2012
DOI: 10.1016/j.jtcvs.2011.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical changes in serum creatinine and mortality after coronary artery bypass grafting

Abstract: Subclinical increases in serum creatinine that do not meet acute renal injury criteria are independently associated with 30-day all-cause mortality in patients with normal renal function or preoperative renal insufficiency undergoing coronary artery bypass grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 22 publications
3
57
1
Order By: Relevance
“…We excluded 268 studies: animal studies (15), reviews (42), no epidemiological data available (177), not about CRS-1 (23), no data about AKI or WRF (8) and studies evaluating a specific intervention (3). Finally, we included 64 papers (n = 509,766 patients), containing data on AKI in AHF patients (18 studies; 29,202 patients) [4,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26], ACS (15 studies; 282,113 patients) [13,27,28,29,30,31,32,33,34,35,36,37,38,39,40] and CS (32 studies; 198,451 patients) [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72] (table 1). One study contained information about AHF as well as ACS and is therefore used in both groups [13].…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 268 studies: animal studies (15), reviews (42), no epidemiological data available (177), not about CRS-1 (23), no data about AKI or WRF (8) and studies evaluating a specific intervention (3). Finally, we included 64 papers (n = 509,766 patients), containing data on AKI in AHF patients (18 studies; 29,202 patients) [4,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26], ACS (15 studies; 282,113 patients) [13,27,28,29,30,31,32,33,34,35,36,37,38,39,40] and CS (32 studies; 198,451 patients) [41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72] (table 1). One study contained information about AHF as well as ACS and is therefore used in both groups [13].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have linked minor creatinine increases to higher mortality in small subsets of cardiac surgery patients. These studies categorized patients by absolute creatinine increases, 21,34,36 by relative creatinine increase 32,37 or by AKI stages. 38,39 Although explicitly accounting for minor creatinine changes, the patients identified as "at risk" were either likely to be diagnosed as stage 1 AKI by current AKI definition or the study failed to identify all patients at risk.…”
Section: Discussionmentioning
confidence: 99%
“…2 In addition, the resemblance of our study's results to those of previous studies in smaller patient samples and in elect surgical subpopulations further supports our conclusions. [20][21][22]34,36,57 …”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…The latter findings turned out to be particularly significant as several studies describe even subclinical changes in serum creatinine as an independent risk factor for all cause 30-day mortality after cardiac surgery. 2,3 A recent multicenter study revealed that perioperative creatinine levels are superior in detection of CSA-AKI in comparison with cystatin C. 38 Therefore, we chose the perioperative creatinine increase as the primary endpoint for multiple regression analyses and the subsequent power analyses. The additional analyses of the RIFLE criteria revealed also no significant genetic influence.…”
Section: Cardiac Surgery-associated Acute Kidney Injurymentioning
confidence: 99%
“…2,3 Novel biomarkers for acute renal failure are on the horizon. 4 Nevertheless, the variability in the clinical outcome makes it difficult to predict the risk for an individual patient.…”
Section: Introductionmentioning
confidence: 99%